PTK7: an underestimated contributor to human cancer - Jin, Zhipeng; Guo, Tianyu; Zhang, Xue; Wang, Xin; Liu, Yefu (Frontiers in Oncology, 2024)
Protein tyrosine kinase 7 (PTK7) is an evolutionarily conserved transmembrane receptor and a specialized tyrosine kinase protein lacking kinase activity. PTK7 has been found to be strongly associated with a variety of diseases, including cancer. In this review, we will provide a comprehensive overview of the involvement of PTK7 in human cancer, focusing on the changing research landscape of PTK7 in cancer research, the molecular mechanisms of PTK7 involved in cancer progression, the targetability of PTK7 in cancer therapy, and the potential application of PTK7 in cancer management, thus demonstrating that PTK7 may be an underestimated contributor to human cancer.